2022
DOI: 10.1002/slct.202201229
|View full text |Cite
|
Sign up to set email alerts
|

Bis(thio)carbohydrazone Luminogens with AIEE and ACQ Features and Their In Silico Investigations with SARS‐CoV‐2

Abstract: Herein, we report two novel multidentate luminogen proligands bis(3,5‐diiodosalicylidene) carbohydrazone (H4L1) and bis(3,5‐diiodosalicylidene) thiocarbohydrazone (H4L2), which are suitable candidates for biomedical applications. Though the thiocarbohydrazone H4L2 shows aggregation caused quenching (ACQ), the carbohydrazone H4L1 exhibits stronger fluorescence due to aggregation induced emission enhancement (AIEE). Molecular docking studies of H4L1 and H4L2 along with four similar (thio)carbohydrazones with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…The positive or electron-deficient NH region is represented by the blue or cyan areas and is available for nucleophilic attack. 51 It is still highly instructive regarding areas where the ligand may come into contact with the electrophile.…”
Section: Resultsmentioning
confidence: 99%
“…The positive or electron-deficient NH region is represented by the blue or cyan areas and is available for nucleophilic attack. 51 It is still highly instructive regarding areas where the ligand may come into contact with the electrophile.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that some thiosemicarbazone compounds have antiviral effects on the SARS-CoV-2 as bioinformatically. [31][32][33] The effects of complex 2 on cell viability in BEAS-2B cells were measured by MTT cell viability test. As a result of the experiments, it was found that 2 had a proliferative effect at low doses.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that some thiosemicarbazone compounds have antiviral effects on the SARS‐CoV‐2 as bioinformatically. [ 31–33 ]…”
Section: Resultsmentioning
confidence: 99%
“…18 Its applications range from improved bioimaging to the development of innovative biosensors and the deeper exploration of biomolecular interactions. 5,8 AIE luminogen's distinctive ability to enhance fluorescence upon aggregation offers a range of exciting possibilities for anticancer applications. 19–21 Also, the investigation of new luminescent probes capable of binding to SARS-CoV-2 holds immense potential for enhancing the sensitivity of coronavirus detection.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds that demonstrate the AIE phenomenon possess significant potential as valuable assets in the battle against COVID-19. 8,28…”
Section: Introductionmentioning
confidence: 99%